Overexpression of natural killer group 2 member D ligands predicts favorable prognosis in cholangiocarcinoma. Issue 2 (2nd February 2016) - Tsukagoshi, Mariko; Wada, Satoshi; Yokobori, Takehiko; Altan, Bolag; Ishii, Norihiro; Watanabe, Akira; Kubo, Norio; Saito, Fumiyoshi; Araki, Kenichiro; Suzuki, Hideki; Hosouchi, Yasuo; Kuwano, Hiroyuki
Abstract : The natural killer group 2 member D (NKG2D) receptor and its ligands are important mediators of immune responses to tumors. NKG2D ligands are overexpressed in several malignant tumor types; however, the prognostic value of these ligands is unclear. Here, we aimed to elucidate the role of NKG2D ligands in extrahepatic cholangiocarcinoma (EHCC). We therefore investigated the expression of the NKG2D receptor and its ligands MHC class I chain‐related proteins A and B (MICA/B), unique long 16 binding protein (ULBP) 1, and ULBP2/5/6 in resected specimens from 82 patients with EHCC. All NKG2D ligands were highly expressed in EHCC. High expression of MICA/B or ULBP2/5/6 correlated with overall and disease‐free survival. In contrast, high expression of ULBP1 was significantly associated with improved overall survival, but not disease‐free survival. Concurrent high expression of multiple NKG2D ligands revealed significantly better overall and disease‐free survival than that observed with the overexpression of any one NKG2D ligand. Co‐expression of multiple NKG2D ligands was an independent prognostic indicator of improved survival. Furthermore, co‐overexpression of multiple NKG2D ligands was significantly correlated with high expression of the NKG2D receptor. Inhibiting interactions between multiple NKG2D ligands and the NKG2D receptor might be a promising approach for controlling cancer progression and improving patient prognosis in EHCC. Abstract : High expression of multiple NKG2D ligands was associated with a good prognosis in extrahepatic cholangiocarcinoma and was correlated with high expression of the NKG2D receptor. Interactions between NKG2D and multiple NKG2D ligands were important for inhibiting extrahepatic cholangiocarcinoma progression.